The distribution of BCG prostatitis: A clue for pathogenetic processes?. Issue 15 (10th July 2018) - Butel, Ryan; Ball, Richard
Abstract : Background: We observed in cystoprostatectomy specimens that Bacillus Calmette‐Guérin (BCG) granulomatous prostatitis tended preferentially to affect the peripheral zone (PZ) and aimed to study the matter, postulating that assessment of its distribution might contribute to understanding pathogenetic processes. Methods: Entire prostate glands from 27 men (47‐83 years; mean = 69 years), who had previously received intravesical BCG therapy for non‐muscle‐invasive urothelial carcinoma of the bladder, were studied as whole‐mount sections to determine the anatomical distribution and histopathological characteristics of BCG prostatitis. Results: Twenty‐two (81.5%) showed BCG‐type granulomatous inflammation. It often radiated from close to the prostatic urethra toward to the gland periphery as a wedge‐shaped area related to one or more duct systems. Twenty‐one of these prostate glands (95.5%) showed predominantly or exclusively PZ involvement. Eighteen (81.8%) involved only the PZ, while three cases (13.6%) also showed involvement of the transitional zone (TZ). One case (4.5%) involved only the TZ. No granulomas were seen in the central zone or anterior fibromuscular septum. Conclusions: Our observations imply the microanatomical arrangement of prostatic ducts is a factor in the pathogenesis of BCG prostatitis. PZ ducts enter the urethra at less obtuse angles than those from other zones and are likely to be more prone to urine reflux and damage from suspended BCG. We speculate that prostatic duct microanatomy could also play a role in the pathogenesis of other prostatic diseases, including conventional prostatitis and adenocarcinoma.